تحديد القيم الشاذة باستخدام الطرق الاستكشافية ومقارنتها مع الطرق المعلمية - حسن, محمود مهدي; دغا, دلير صليوا (Journal of Economics and Administrative Sciences, 2008)
The availability of statistical data plays an important role in planning process. The importance of this research which deals with safety of statistical data from errors and outliers values. The Objective of this study is to determine the outlier values in statistical data by using modern exploratory data methods and comparing them with parametric methods. The research has been divided into four chapters ,the main important conclusions reached are:1-The exploratory methods and the parametric methods showed variation between them in determining the outlier values in the data.2-The study showed that the box plot method was the best method used in determining outlier values in data.